Mobile App for the Promotion of Home Services - Nicolás Quispe, David Israel (2020)
Home services advertising presents difficulties to the worker who has as an obstacle the cost of the advertising used to promote his services so that a large amount of people can see it, as well as the deficient training in technological tools has brought as consequence the usage of traditional methods which made being located and hired in real time more difficult. In this sense, the objective of this research was to develop and implement a mobile application that allows home services advertising and is able to fulfill all the previous mentioned factors; XP methodology was used for the development of the application; ten cases were used as evidence where demonstrated it was capable of advertising household services, which concludes that the mobile application can advertise household services.